(3GdEOGQI GdEdcJQhfjIs - (3eMeO(B, (3GdUjQajs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj,s, 2006)
(3GdMcheI GdGdcJQhfjI, GdCYeGd GdGdcJQhfjI, GdJShjb GdGdcJQhfjs
(3eQGLY U(B.789s
Keywords: (3GdEOGQI(B- (3GdCLgRI GdEdcJQhfjI s; (3GdGOGQIs; (3GdMcheGJs